Petrogenesis and tectonic implication of the Late Triassic post-collisional volcanic rocks in Chiang Khong, NW Thailand - Qian, X.; Wang, Y.; Feng, Q.; Zi, Jianwei; Zhang, Y.; Chonglakmani, C. (Elsevier BV, 2016)
The volcanic rocks exposed within the Chiang Khong-Lampang-Tak igneous zone in NW Thailand provide important constraints on the tectonic evolution of the eastern Paleotethys ocean. An andesite sample from the Chiang Khong area yields a zircon U-Pb age of 229 ± 4 Ma, significantly younger than the continental-arc and syn-collisional volcanic rocks (ca. 238-241 Ma). The Chiang Khong volcanic rocks are characterized by low MgO (1.71-6.72 wt.%) and high Al2O3 (15.03-17.76 wt.%). They are enriched in LILEs and LREEs and depleted in HFSEs, and have 87Sr/86Sr (i) ratios of 0.7050-0.7065, eNd (t) of -0.32 to -1.92, zircon eHf (t) and d18O values of 3.5 to -11.7 and 4.30-9.80 ‰, respectively. The geochemical data for the volcanic rocks are consistent with an origin from the enriched lithospheric mantle that had been modified by slab-derived fluid and recycled sediments. Based on available geochronological and geochemical evidences, we propose that the Late Triassic Chiang Khong volcanic rocks are equivalent to the contemporaneous volcanic rocks in the Lancangjiang igneous zone in SW China. The formation of these volcanic rocks was possibly related to the upwelling of the asthenospheric mantle during the Late Triassic, shortly after slab detachment, which induced the melting of the metasomatized mantle wedge.